2003
DOI: 10.1021/jf034791a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Six Phenylpropanoids from Garlic Skin as Major Antioxidants

Abstract: The extract of garlic skins (peels) showed strong antioxidant activity, and some responsible constituents were isolated and identified. Garlic (Allium sativum L.) has been used as an herbal medicine, but there is no report on the health benefits of the skin or peel. In this study, the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of garlic skin extract was evaluated. Using chromatographic techniques, the active constituents were isolated and subsequently identified. Analyses by high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 12 publications
7
46
0
1
Order By: Relevance
“…Not only AGE possesses antioxidant activity. In addition, the extract of garlic skins (peels) has the same properties [85]. In this study, the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of garlic skin extract was evaluated.…”
Section: Garlic and Plasma Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Not only AGE possesses antioxidant activity. In addition, the extract of garlic skins (peels) has the same properties [85]. In this study, the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of garlic skin extract was evaluated.…”
Section: Garlic and Plasma Antioxidant Activitymentioning
confidence: 99%
“…LC-MS and NMR analyses allowed the chemical structures of the isolated constituents to be postulated. The proposed compounds were subsequently synthesized and compared with the constituents in the extract using HPLC-PDA and LC-MS. N-trans-coumaroyloctopamine, N-trans-feruloyloctopamine, guaiacylglycerol-betaferulic acid ether, and guaiacylglycerol-beta-caffeic acid ether were identified as were trans-coumaric acid and transferulic acid [85].…”
Section: Garlic and Plasma Antioxidant Activitymentioning
confidence: 99%
“…Pant et al [17] found that Arabidopsis thaliana plants contain two phenylpropanoids, cis-sinapic acid and trans-ferulic acid and the fatty acid octadecanoic acid. N-trans-coumaroyloctopamine, N-transferuloyl octopamine, guaiacylglycerol-β-ferulic acid ether, guaiacylglycerol-β-caffeic acid ether, trans-coumaric acid and transferulic acid were identified in garlic skin [22]. While hexadecanoic acid and octadecanoic acid are the fatty acids found in Melissa officinalis [23].…”
Section: Resultsmentioning
confidence: 98%
“…Many of the chemical constituents present in Allium sativum (garlic) are known (Amagase, 2006). From the garlic skin, the part used in 'Tira-capeta', were isolated phenylpropanoids (Ichikawa et al, 2003(Ichikawa et al, , 2006 and flavonoids (Stajner et al, 2006). Of the two remaining plants, Anemopaegma arvense ('alecrimdo-norte') and Hyptis cana ('hortelã-da-várzea'), there are no phytochemical data in the literature, but we suppose that they possess tannins, flavonoids and saponins, since they are the major constituents of ETC.…”
Section: Catalepsy Testmentioning
confidence: 99%